Kredi Kartlarının Temerrüde Düşmesini Etkileyen Makro Ekonomik Değişkenler: Türkiye Üzerine Ekonometrik Bir Analiz - TUNAY, KAŞİF BATU; TUNAY, NECLA (My University, 2023)
In this study, macroeconomic variables that may have an effect on the default of credit cards in Turkey and their effect levels were investigated. Two separate data sets, consisting of quarterly and monthly data covering the period 2013-2022, were analyzed. Seah et al.(2014) a regression model they developed was adapted for Turkey. In this model, an autoregressive error mechanism is used as well as macroeconomic variables, and the past dependence of prediction errors is taken into account. Since the analyzed models arenon-linear, parameter estimations are performed with the ML estimator. It has been observed that increases in income level and interest rates decrease the default rate of credit cards. On the other hand, an inverse relationship was found between the inflation rate and the default rate of credit cards. Whether inflation rates increase or not, credit card default rates will not increase unless the economy enters a recession. It is predicted that the default rates may increase if the economy shrinks and unemployment rates increase. It has also been determined that the estimation errors show a strong and positive dependence to the past.Keywords:Credit cards, default of credit cards, macroeconomic determinants, regressionanalysis

Bu çalışmada, Türkiye’de kredi kartlarının temerrüde düşmesi üzerinde etkili olabilecek makro ekonomik değişkenler ve bunların etki düzeyleri araştırılmıştır. 2013-2022 dönemini kapsayan üç aylık ve aylık verilerden oluşan iki ayrı veri seti analiz edilmiştir. Analizler kapsamında, Seah vd. (2014) tarafından geliştirilen bir regresyon modeliTürkiye’ye uyarlanmıştır. Bu modelde, makro ekonomik değişkenler yanında ardışık bağlanımlı bir hata mekanizması da kullanılmış ve tahmin hatalarının geçmişe bağlılıkları dikkate alınmıştır. Analiz edilen modeller doğrusal olmadıklarından, parametre tahminleri EYO tahmincisiyle yapılmıştır. Bulgular incelendiğinde, gelir düzeyindeki ve faiz oranlarındaki artışların kredi kartlarının temerrüde düşme oranını azalttığı gözlenmiştir. Diğer yandan, enflasyon oranıyla kredi kartlarının temerrüde düşme oranı arasında ters bir ilişkinin varlığı saptanmıştır. Enflasyon oranları artsın veya artmasın, ekonomi durgunluğa girmedikçe kredi kartlarının temerrüde düşme oranları yükselmeyecektir. Ekonominin daralması ve işsizlik oranlarının artması halinde temerrüt oranlarının artabileceği öngörülmektedir. Ayrıca tahmin hatalarının güçlü ve pozitif bir geçmişe bağlılık gösterdikleri de belirlenmiştir.Anahtar Kelimeler:Kredi kartları, kredi kartlarının temerrüde düşmesi, makro ekonomik belirleyiciler, regresyon analizi
Macro-economic variables affecting the default of credit cards: an econometric analysis on turkey
Keywords: Kredi kartları; kredi kartlarının temerrüde düşmesi; makro ekonomik belirleyiciler; regresyon analizi; Credit cards; default of credit cards; macroeconomic determinants; regressionanalysis